Prevalence of irregular red cell antibody in transfusion recipients vis-a-vis healthy blood donors attending a tertiary care hospital in North India - Abhilasha Yadav; Gaurav Raturi; Bhardwaj Aparna (Asian Journal of Transfusion Science, 2022)
CONTEXT: Alloimmunization by foreign red cell antigens is a matter of concern as it may lead to hemolysis in transfused patients as well as fetus of pregnant females. AIMS: This study aimed to perform a comparative analysis of prevalence and type of irregular antibodies in healthy donors, vis-a-vis blood transfusion recipients. SETTINGS AND DESIGN: Blood samples of 4000 individuals comprising healthy donors, exposed patients, and nonexposed patients were collected and were analyzed for irregular antibodies. MATERIALS AND METHODS: Commercially available three-cell antigen panel was used for the antibody screening. The samples positive in antibody screen were further subjected to an extended 11-cell panel for antibody identification in low-ionic strength saline with and without enzyme. STATISTICAL ANALYSIS: Statistical analysis was done using SPSS for Windows 15.0 program. Chi-square test was used for detecting statistical significance of exposure to red blood cell antigens in the formation of alloantibodies. RESULTS: Of the 4000 samples, antibodies were identified in 105 (2.6%) samples. Overall, nonexposed group showed a seropositivity of 0.36%, while the exposed group showed a seropositivity of 9.4%. Anti-D was the most common antibody found in 38 patients (33.3%). Anti-E was the most common antibody in males, while anti-D was the most common antibody in females. CONCLUSIONS: Since the risk of alloimmunization is more common in multitransfused patients, it is advisable to screen at least those cases for irregular antibodies.